(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
It necessary to remove heavy metals from wastewater in order to comply with environmental regulations and for sake of human health and safety. The purposes of the present study was to prepare hybrid modified adsorbent from the carbonized palm shell and rice husk by physical treatment for the removal of 13 multi heavy metal component from simulated wastewater by single bed adsorption column. The Metals being studied are Cadmium, Chromium, Copper, Iron, Magnesium, Manganese, Lead, Lithium, Molybdenum, Nickel, Antimony, Vanadium and zinc. Six types of adsorbents were used for metal removal which are (100% BRH) adsorbent; (100% CPS) adsorbent , and four hybrids adsorbent prepared by mixing the blended rice husk and carbonized palm kernel shell with mixing ratios 20% , 40% , 60% , 80% wt Blended Rice Husk . The obtained results of the individual area under the graph analysis showed that cadmium, copper, lithium; vanadium elements were strongly adsorbed by hybrid adsorbents with achieved removal efficiency of 99.95%, 99.97%, 31.23%, and 89.58% with least area under the graph values of 3294.65, 2015.52, 118.231, and 115.18 respectively. As a conclusion, the mixing of blended rice husk and carbonized palm shell as hybrid adsorbent contributed to enhance the adsorption performance of cadmium, copper, lithium, vanadium, elements which demonstrated by less area under the graph values compared with pure carbonized palm shell and pure rice husk adsorbents.